Public concerns, environmental standards, and agricultural trade [ - Brouwer, Floor (CABI, 2002)
This book reviews issues about the quality of the environment in relation to agriculture, and relates them to agricultural trade and competition. It focuses primarily on the key environmental and human-health issues (e.g., pollution from agriculture, th quality of landscapes, animal welfare, and food safety) affecting agriculture in the EU, USA, Canada, Australia, and New Zealand. It also reviews the policy measures and standards established in these countries. The book contains 11 chapters and a subject index.